Cometabolic degradation and inhibition kinetics of 1,2-dichloroethane (1,2-DCA) in suspended-growth nitrifying systems - KOCAMEMİ, BİLGE (TAYLOR & FRANCIS LTD, 2010)
Cometabolic degradation of 1,2-dichloroethane (1,2-DCA) and its inhibitory impact on nitrification were investigated by the use of a mixed suspended-growth culture enriched for nitrifiers. 1,2-DCA was found to be cometabolically degradable by the nitrifier culture. This degradation rate was found to be dependent on the initial 1,2-DCA level. The first-order 1,2-DCA degradation rate constants ranged between 0.42 and 0.87 L (g VSS)(-1) h(-1). Increase in NH4-N utilization favoured cometabolic degradation of 1,2-DCA. The amount of 1,2-DCA degraded per unit mass of NH4-N strongly correlated with initial NH4-N and 1,2-DCA concentrations, ranging between 50 mg L-1 and 200 mg L-1 and 1600 mu g L-1 and 100,000 mu g L-1, respectively. The presence of 1,2-DCA caused inhibition of oxygen uptake and NH4-N utilization. In spite of the adverse effect of 1,2-DCA on the nitrifying biomass, the system had a high capacity for cometabolic removal of this compound even at inhibitory concentrations. 1,2-DCA had mainly mixed inhibitor characteristics, but at low concentrations (<25,000 mu g/L) it acted rather as a competitive inhibitor. The inhibition constants belonging to 1,2-DCA, K-ic (the dissociation constant of the enzyme-inhibitory compound complex) and K-iu (the dissociation constant of the enzyme-substrate-inhibitory compound complex) were determined to be 6000-8000 mu g L-1 and 188,000200,000 mu g L-1, respectively.
Keywords: activated sludge; biodegradation; cometabolism; nitrification; inhibition; 1,2-dichloroethane; XANTHOBACTER-AUTOTROPHICUS GJ10; NITROSOMONAS-EUROPAEA; AEROBIC COMETABOLISM; CHLORINATED SOLVENTS; MIXED CULTURE; TRICHLOROETHYLENE; TCE; 1,1,1-TRICHLOROETHANE; MONOOXYGENASE; INACTIVATION